4x+x+2=10x-5x+2

Simple and best practice solution for 4x+x+2=10x-5x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+x+2=10x-5x+2 equation:


Simplifying
4x + x + 2 = 10x + -5x + 2

Reorder the terms:
2 + 4x + x = 10x + -5x + 2

Combine like terms: 4x + x = 5x
2 + 5x = 10x + -5x + 2

Reorder the terms:
2 + 5x = 2 + 10x + -5x

Combine like terms: 10x + -5x = 5x
2 + 5x = 2 + 5x

Add '-2' to each side of the equation.
2 + -2 + 5x = 2 + -2 + 5x

Combine like terms: 2 + -2 = 0
0 + 5x = 2 + -2 + 5x
5x = 2 + -2 + 5x

Combine like terms: 2 + -2 = 0
5x = 0 + 5x
5x = 5x

Add '-5x' to each side of the equation.
5x + -5x = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -5x-(4x-4)=31 | | 2n+3=4n+9 | | A=ha | | t-(5t-3)=-9 | | (5y/3)^2-y^2=21 | | t-(5t+3)=-9 | | (-2x+7)(7x+2)=0 | | -1-(-3+5n)=7-5(4+4n) | | -(3x+2)-(3x-4)=-8-(2x+2) | | 11x-8+2x+3=x+4+12x-9 | | 0.32x+0.39y=3.62 | | (2x-7)(-7x-2)=0 | | -(2x-1)-(4x+4)=-10-(2x+5) | | 3(y-3)-(5y-2)=4(3y-3)-9 | | 3(y-4)-(2y-3)=4(2y+2)+11 | | -5-2p=-4 | | Ax+B=2A-5x | | 6x+(-2)(2)=18 | | 0.4a+.5(20-a)=9.5 | | 6x+2(2)=18 | | 5(1-2b)+5(2b+5)=1 | | 0.1a+0.2(12-a)=1.9 | | 6x-2(-1)=18 | | 11xy-4xy-7xy= | | F(x)=x/11x^2-8 | | 6x-2(2)=18 | | 18x=75+10x | | 1-3.61x=1.068-1.73x | | 8+x=49 | | 48x-x^2=60y-y^2-xy | | y^2-60y+xy+48x-x^2=0 | | 101x-201465=950000000 |

Equations solver categories